Sustainable buildings and structures : building a sustainable tomorrow : proceedings of the 2nd International Conference in Sustainable Buildings and Structures, Suzhou, China, 25-27 October 2019 /: building a sustainable tomorrow : proceedings of the 2nd International Conference in Sustainable Buildings and Structures, Suzhou, China, 25-27 October 2019. ([2020]) - Unknown
No abstract available